Sosialisasi Perbankan Syariah di Desa Cijambu Kecamatan Tanjungsari Kabupaten Sumedang - Triadi Abidin, Mario Aldo; Muslimah, Sarah (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2022)
The growth of Islamic banking in Indonesia is so rapid along with the increasingly sophisticated industrial technology at this time. However, it is very unfortunate that the majority of people in Cijambu Village do not understand this sharia-based financial institution. Even though there are many products and services of Islamic banks that can provide benefits and benefits for their customers. In this way, it is necessary to carry out the Socialization of Sharia Banking in Cijambu Village, Kec. Tanjungsari Kab. Sumedang. This study uses the Participatory Action Research (PAR) approach. The volunteers took part in the socialization and were quite enthusiastic about listening to the presentation material. This is evidenced by the response of the public in answering the questions raised in the discussion session, the enthusiasm in providing answers to the questions asked showed that the information submitted was well received by the participants, so that the problem of understanding Islamic banks which was still low was successfully explained and people become aware of Islamic banking. After the dissemination of Islamic banking, the public also knows and prevents them from borrowing money from emok banks, moneylenders, and so on, as well as because it is not in accordance with Islamic Sharia and members for lending because the interest offered is higher in returning the funds.